The “Trojan Horse” Approach to Tumor Immunotherapy: Targeting the Tumor Microenvironment - Nelson, Delia; Fisher, S.; Robinson, B. (Hindawi Publication Corporation, 2014)
Most anticancer therapies including immunotherapies are given systemically; yet therapies given directly into tumors may be more effective, particularly those that overcome natural suppressive factors in the tumor microenvironment. The “Trojan Horse” approach of intratumoural delivery aims to promote immune-mediated destruction by inducing microenvironmental changes within the tumour at the same time as avoiding the systemic toxicity that is often associated with more “full frontal” treatments such as transfer of large numbers of laboratory-expanded tumor-specific cytotoxic T lymphocytes or large intravenous doses of cytokine. Numerous studies have demonstrated that intratumoural therapy has the capacity to minimizing local suppression, inducing sufficient “dangerous” tumor cell death to cross-prime strong immune responses, and rending tumor blood vessels amenable to immune cell traffic to induce effector cell changes in secondary lymphoid organs. However, the key to its success is the design of a sound rational approach based on evidence. There is compelling preclinical data for local immunotherapy approaches in tumor immunology. This review summarises how immune events within a tumour can be modified by local approaches, how this can affect systemic antitumor immunity such that distal sites are attacked, and what approaches have been proven most successful so far in animals and patients.